Recombinant human L-ficolin directly neutralizes hepatitis C virus entry - Hamed, Mohamed R.; Brown, Richard J.P.; Zothner, Carsten; Urbanowicz, Richard A.; Mason, Christopher P.; Krarup, Anders; McClure, C. Patrick; Irving, William L.; Ball, Jonathan K.; Harrison, Mark; Hickling, Timothy P.; Tarr, Alexander W. (Karger, 2014)
L-ficolin is a soluble pattern recognition molecule expressed by the liver that contributes to innate immune defense against microorganisms. It is well described that binding of L-ficolin to specific pathogen-associated molecular patterns activates the lectin complement pathway, resulting in opsonization and lysis of pathogens. In this study, we demonstrated that in addition to this indirect effect, L-ficolin has a direct neutralizing effect against hepatitis C virus (HCV) entry. Specific, dose-dependent binding of recombinant L-ficolin to HCV glycoproteins E1 and E2 was observed. This interaction was inhibited by soluble L-ficolin ligands. Interaction of L-ficolin with E1 and E2 potently inhibited entry of retroviral pseudoparticles bearing these glycoproteins. L-ficolin also inhibited entry of cell-cultured HCV in a calcium-dependent manner. Neutralizing concentrations of L-ficolin were found to be circulating in the serum of HCV-infected individuals. This is the first description of direct neutralization of HCV entry by a ficolin and highlights a novel role for L-ficolin as a virus entry inhibitor.